Coping with Urban Climates Comparative Perspectives on Architecture and Thermal Governance - Roesler, Sascha; Kobi, Madlen; Stieger, Lorenzo (Klima Polis, 2022)
While 20th century architecture learned to control the climate of a building, the architecture of the 21st century needs to learn to cope with the climate of cities. Problems such as urban heat and air pollution need to be included in planning and design. The book argues for a new type of "thermal governance" that considers the interdependency of climatic and socio-economic phenomena in contemporary cities.